Impact Factors in a Curriculum Vitae for Scholarship Application - Giang, Hoang Thi Nam (IIUM Medical Journal Malaysia, 2023)
Introduction. Scholarship applicants often receive different advice on what should be included in their Curriculum Vitae (CV). This study aims to investigate what the essential components of a CV being prepared for scholarships are, how to present them, and what their level of impact is. Materials and Methods. The authors sent an online structured questionnaire to 7512 corresponding authors of recent published papers in Scopus; 124 completed questionnaires were returned. Recommended elements for a CV were chosen according to the Delphi consensus technique with a threshold of 50%. Results. This survey revealed that headings, bullet points and careful error checking were essential parts of the layout. For the content of the CV, besides publications, education and training background, research experience and research interest were also necessary. Moreover, almost all respondents ranked publications as the most important qualification of an academic scholarship candidate. Publications also came first as the most impressive factor, followed by awards and honours. The number of publications, quality of journal, impact factor and total citation should be presented in publication section. The importance of publications in getting academic scholarships is significantly emphasized in this recent study. Conclusions. Having research experience and papers in peer review journals, are highly recommended for students seeking academic scholarships.